Aβ1-40-Induced Platelet Adhesion Is Ameliorated by Rosmarinic Acid through Inhibition of NADPH Oxidase/PKC-δ/Integrin αIIbβ3 Signaling - Bo Kyung Lee; Hye Jin Jee; Yi-Sook Jung (MDPI AG, 2021)
In platelets, oxidative stress reportedly increases platelet adhesion to vessels, thus promoting the vascular pathology of various neurodegenerative diseases, including Alzheimer's disease (AD). Recently, it has been shown that β-amyloid (Aβ) can increase oxidative stress in platelets; however, the underlying mechanism remains elusive. In the present study, we aimed to elucidate the signaling pathway of platelet adhesion induced by Aβ1-40, the major form of circulating Aβ, through Western blotting, immunofluorescence confocal microscopy, and fluorescence-activated cell sorting analysis. Additionally, we examined whether rosmarinic acid (RA), a natural polyphenol antioxidant, can modulate these processes. Our results show that Aβ1-40-induced platelet adhesion is mediated through NADPH oxidase/ROS/PKC-δ/integrin αIIbβ3 signaling, and these signaling pathways are significantly inhibited by RA. Collectively, these results suggest that RA may have beneficial effects on platelet-associated vascular pathology in AD.